Delay-Tolerant, Low-Power Protocols for Large Security-Critical Wireless Sensor Networks - Claudio S. Malavenda; F. Menichelli; M. Olivieri (Journal of Computer Networks and Communications)
This paper reports the analysis, implementation, and experimental testing of a delay-tolerant and energy-aware protocol for a wireless sensor node, oriented to security applications. The solution proposed takes advantages from different domains considering as a guideline the low power consumption and facing the problems of seamless and lossy connectivity offered by the wireless medium along with very limited resources offered by a wireless network node. The paper is organized as follows: first we give an overview on delay-tolerant wireless sensor networking (DTN); then we perform a simulation-based comparative analysis of state-of-the-art DTN approaches and illustrate the improvement offered by the proposed protocol; finally we present experimental data gathered from the implementation of the proposed protocol on a proprietary hardware node.